THE ROLE OF SOIL MICROBIOCENOSIS IN THE COMPOSTING OF THE ORGANIC COMPONENT OF THE MUNICIPAL SOLID WASTE - G. Krusir; T. Shpyrko; О. Sagdeeva; V. Zakharchuk (Harčova Nauka ì Tehnologìâ, 2019)
In order to increase the efficiency of composting the organic component of solid municipal waste as a highly effective biotechnological method, and to compare the characteristics of the processes, it is suggested to use soil as an inoculum, as a microbiological additive - an extract from the soil. The original compost mixture is a multicomponent system, the decomposition and transformation of which depends on the functioning of a microorganisms complex, in particular, fungal and bacterial microflora. Since the main component of the organic fraction is cellulose, it is expedient, along with the definition of the total number of the microflora bacterial and fungal components, to determine the number of cellulose-decomposing microorganisms. An estimation of the change in the compost mixtures’ microbial population has been made, which shows that bacteria dominate over fungi in compost mixtures. A similar microbial complex is observed in soils. The article presents the results of the study of the soil microbiocenosis qualitative and quantitative composition in order to use it as an inoculum in the process of composting the organic part of solid municipal waste. The influence of microbiological additive on the process of the organic waste composting for acceleration in mesophilic and thermophilic temperature regimes with controlled parameters was studied. The results of the conducted studies allow us to conclude that the organic waste composting with the microbiological additive is appropriate, both in the case of thermophilic and in the case of mesophilic regimes. The period of the compost maturation with the use of a microbiological additive is 6 weeks. It was shown that the microbiological complex accelerates the process of composting the organic component of solid municipal waste by 3.3 times for the thermophilic regime and by 2.1 times for the mesophilic conditions of composting process, which testifies to the efficiency of its use in the operation of the solid municipal waste processing in order to improve the general level of environmental safety.